Macroinvertebrados bentônicos em córregos da Estação Ecológica de Jataí, Luiz Antônio, SP: subsídios para monitoramento ambiental - Guereschi, Renata Maria (2004)
The Jataí Ecological Station (EEJ), located in Luiz Antônio, State of São Paulo, Brazil, is a Conservation Unit of Indirect Use in an area jeopardized by highly mechanized agriculture and subject to multiple disturbances, which pose threats to its biodiversity. The aim of this work was to evaluate the environmental conditions of the Boa Sorte, Beija-Flor and Cafundó streams in the EEJ and of a stream near this station, in Luiz Antônio, through the study of benthic macroinvertebrates. To this end eight collection sites were established, and sampling was carried out bimonthly from December 2000 to August 2002. The water samples collected were subsequently taken to the lab and had their nutrients and suspended solids analyzed. Other abiotic variables were measured in situ. Artificial substrate was used to capture the benthic macroinvertebrates. The analyses of the physical and chemical variables confirmed the characterization of distinct periods (dry and rainy) and the influence of the overflowing of the Mogi-Guaçu river at the sites located in the flood plain. There were collected 8,072 specimens, distributed among 81 taxonomic units, out of which 36 corresponded to groups of higher categories up to the family level and 46 genus of Chironomidae. The taxocenosis analyses of the benthic macroinvertebrates indicate temporal and spatial differences reflecting the two seasonal periods (dry and rainy), with higher organism densities and taxonomic richness in the dry season. Although most of the taxa were found at all sampling sites, differences in fauna composition were observed, which reflecting the activities developed in every micro-basin monitored in this work.